Rumors as a means of forming an information space in the occupied territory of Ukraine in 1941-1944 - Oksana Salata; Tetyana Ginetova (Київські історичні студії, 2022)
The article examines the phenomenon of rumors, which played an important role in the formation of the information space in the territories occupied by the German army during the Second World War. The analysis of conditions in which rumors arose and functioned is carried out; the peculiarity of rumors created by Nazi and Soviet propaganda is determined; a comparison of their characteristics and impact on the population of the occupied territories of Ukraine in 1941-1943; specific examples show the regularity of the distribution of oral messages transmitted among the Ukrainian population. The general methodological and technical mechanisms of preparation and dissemination of rumors, training of specialists who disseminated them and analyzed the events caused by their influence are shown. It is shown that the German occupation authorities used rumors as weapons. In order to spread rumors and conduct active counter-propaganda, the German government began training psychologists who developed the necessary strategy for using rumors. Based on the analysis of archival materials and literature, it is shown that both sides and the Soviet and German leadership used rumors quite effectively as one of the mechanisms influencing the consciousness of the population of the occupied territories and directly involved in the formation of information space. In addition to word of mouth, the latest technical means, including radio broadcasting, were used to spread rumors. It is concluded that rumors are a serious weapon of any propaganda, in particular in the modern Russian-Ukrainian war. Without knowledge of the laws that determine the emergence and effect of rumors, it is impossible to fight them.